Potential of Traditions and Belief in Almighty God (YME) and Management Strategies for Cultural Resilience in Indonesia - Ruslan, Idrus; Abshar, Rijal Ulil; Isnaeni, Ahmad (Analisis: Jurnal Studi Keislaman, 2024)
The potential for traditions and beliefs in God Almighty in Indonesia reflects cultural richness which includes a variety of traditional and spiritual practices from various tribes and regions. This tradition is not only a cultural heritage, but also a spiritual foundation in people's daily lives. To maintain this cultural diversity, a good and sustainable management strategy is needed. This research is qualitative descriptive analytical, using a holistic approach involving various methods of literature analysis, literature study, and theoretical approaches. The data analysis techniques used include data reduction, data display, and formulating conclusions. The results of the study show that the potential for traditions and belief in God Almighty in Indonesia provides cultural richness through various traditional and spiritual practices from various tribes and regions. This tradition reflects deep spiritual values in everyday life. Management strategies for cultural resilience include comprehensive education about cultural heritage, cross-sector collaboration for the protection and development of traditions, and the use of technology to promote and preserve cultural values.